Agricultural Extension Service and Input Application Intensity: Evidence from Ethiopia - Gebregziabher, Kidane Mariam (Journal of Economics and Behavioral Studies, 2014)
This paper examines factors that influence agricultural input adoption in the northern part of Ethiopia. Using a 730 households survey data set, a Tobit model is estimated to explain the factors that influence farmers’ decision to adopt modern inputs or not. The factors found to significantly influence included: plot size, oxen ownership, gender, age and literacy status of the household head, adult labor force, total non-farm income, extension service and location variables. The results confirm the adoption theory.